A multidimensional framework for understanding problematic use of short video platforms: the role of individual, social-environmental, and platform factors - Xiong, Sihan; Chen, Jing; Yao, Nisha (Frontiers in Psychiatry, 2024)
Short video platforms have rapidly become a prominent form of social media, but their problematic use is increasingly concerning. This review synthesizes existing research to propose a comprehensive framework that integrates individual, social-environmental, and platform-related factors contributing to this issue. Individual factors are categorized into distal (e.g., personality, psychopathology) and proximal (e.g., usage expectations, cognitive, emotional, and behavioral responses during use) categories, with distal factors often shaping proximal ones, which more directly influence usage behaviors. Social-environmental factors, such as family dynamics and peer interactions, along with platform-related features, also significantly impact the likelihood of problematic use. Beyond their direct effects, our framework emphasizes the importance of examining the combined effects of these factors, particularly through mediation and moderation processes. Mediation processes reveal how distal individual factors influence problematic use by shaping more immediate, proximal factors. Similarly, social-environmental influences and platform features may affect problematic use by modifying individual factors. Moderation processes further illustrate how individual characteristics or social-environmental factors may alter the strength of these relationships. Understanding these complex, multidimensional relationships is essential for developing effective interventions to mitigate the risks associated with problematic short video platforms use. Future research should explore these processes in greater depth.